Botulinum toxin and benign prostatic hyperplasia - Lay Guat Ng (Asian Journal of Urology)
Benign prostatic hyperplasia (BPH) is a clinical condition where lower urinary tract symptoms are caused by both a physically obstructing prostate as well as tight smooth muscles around the bladder outlet. Treatment of this condition with botulinum toxin has been used since 2003, but this interest has somewhat died down after two large randomized controlled trials (RCTs) showing equivalence of results between their treatment and placebo arms. However, with review of animal studies and unexplained exaggerated effect of the placebo arms of the two RCTs, together with recent data of sustained benefits after 18 months of treatment, the place of botulinum toxin in the BPH field is probably still present.